Molecular Mechanisms of Plant Responses to Salt Stress - Ma, Liang; Liu, Xiaohong; Lv, Wanjia; Yang, Yongqing (Frontiers in Plant Science, 2022)
Saline-alkali soils pose an increasingly serious global threat to plant growth and productivity. Much progress has been made in elucidating how plants adapt to salt stress by modulating ion homeostasis. Understanding the molecular mechanisms that affect salt tolerance and devising strategies to develop/breed salt-resilient crops have been primary goals of plant salt stress signaling research over the past few decades. In this review, we reflect on recent major advances in our understanding of the cellular and physiological mechanisms underlying plant responses to salt stress, especially those involving temporally and spatially defined changes in signal perception, decoding, and transduction in specific organelles or cells.